Pre and Post Examination Aspects - Plebani, Mario (EJIFCC, 2004)
After a long-standing tradition of analytical quality and analytical quality control programs, most medical laboratories that are aware of the need for total quality management, are experiencing new systems designed to assure quality throughout the entire total testing process, from the pre-analytical to the post-analytical steps. The availability of a new International Standard, ISO 15189:2003, specifically developed and designed to satisfy the requirements for quality management and competence in medical laboratories, should promote the harmonization of accreditation programs at an international level, and implementation of an effective quality system at a local level. The importance of the pre- and post-analytical phases are well recognized in the new International Standard and, therefore, efforts to comply with this standard might assure an approach that safeguards and continuously improves total quality in medical laboratories.